Comparison of Gadoterate Meglumine and Gadobutrol in the MRI Diagnosis of Primary Brain Tumors: A Double-Blind Randomized Controlled Intraindividual Crossover Study (the REMIND Study) - Maravilla, K.R.; San Juan, Daniel; Kim, S.J.; Elizondo Riojas, Guillermo; Fink, J.R.; Escobar, W.; Bag, A.; Roberts, Donald R.; Hao, J.; Pitrou, C.; Tsiouris, A.J.; Herskovits, E.; et al. (American Society of Neuroradiology, 2017)
ABSTRACT BACKGROUNDANDPURPOSE: Effective management of patients with brain tumors depends on accurate detection and characterization of lesions. This study aimed to demonstrate the noninferiority of gadoterate meglumine versus gadobutrol for overall visualization and characterization of primary brain tumors. MATERIALS AND METHODS: This multicenter, double-blind, randomized, controlled intraindividual, crossover, noninferiority study included279patients.Bothcontrastagents(dose=0.1mmol/kgofbodyweight)wereassessedwith2identicalMRIsatatimeintervalof 2–14 days. The primary end point was overall lesion visualization and characterization, scored independently by 3 off-site readers on a 4-point scale, ranging from “poor” to “excellent.” Secondary end points were qualitative assessments (lesion border delineation, internal morphology, degree of contrast enhancement, diagnostic conﬁdence), quantitative measurements (signal intensity), and safety (adverse events). All qualitative assessments were also performed on-site. RESULTS: Forall3readers,imagesofmostpatients(>90%)werescoredgoodorexcellentforoveralllesionvisualizationandcharacterizationwitheithercontrastagent;andthenoninferiorityofgadoteratemeglumineversusgadobutrolwasstatisticallydemonstrated.No signiﬁcant differences were observed between the 2 contrast agents regarding qualitative end points despite quantitative mean lesion percentageenhancementbeinghigherwithgadobutrol(P<.001).Diagnosticconﬁdencewashigh/excellentforallreadersin>81%ofthe patientswithbothcontrastagents.Similarpercentagesofpatientswithadverseeventsrelatedtothecontrastagentswereobservedwith gadoterate meglumine (7.8%) and gadobutrol (7.3%), mainly injection site pain. CONCLUSIONS: Thenoninferiorityofgadoteratemeglumineversusgadobutrolforoverallvisualizationandcharacterizationofprimary brain tumors was demonstrated.